2017
DOI: 10.15190/d.2017.6
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence versus Doctors’ Intelligence: A Glance on Machine Learning Benefaction in Electrocardiography

Abstract: Computational machine learning, especially selfenhancing algorithms, prove remarkable effectiveness in applications, including cardiovascular medicine. This review summarizes and cross-compares the current machine learning algorithms applied to electrocardiogram interpretation. In practice, continuous real-time monitoring of electrocardiograms is still difficult to realize. Furthermore, automated ECG interpretation by implementing specific artificial intelligence algorithms is even more challenging. By collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Moreover, these technologies are also frequently used in monitoring activities that would affect the health status of an individual, like measuring heart rate during physical activities and monitoring sugar level and blood pressure readings [15], [16]. Hence, a trustworthy intelligent system should be able to showcase impressive findings that are related to health based on an individual's daily routine behavior [17], [18]. However, existing studies indicated that that need to be resolved for further improvements and these issues represent the loose holes that present in the analytics of life diseases through technology-oriented solutions [4], [5].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these technologies are also frequently used in monitoring activities that would affect the health status of an individual, like measuring heart rate during physical activities and monitoring sugar level and blood pressure readings [15], [16]. Hence, a trustworthy intelligent system should be able to showcase impressive findings that are related to health based on an individual's daily routine behavior [17], [18]. However, existing studies indicated that that need to be resolved for further improvements and these issues represent the loose holes that present in the analytics of life diseases through technology-oriented solutions [4], [5].…”
Section: Introductionmentioning
confidence: 99%
“…Neural networks are as effective as certified dermatologists in differentiating benign neoplasms from malignant neoplasms on photographic and dermatoscopic images [30]. AI can be used to evaluate electrocardiograms [31] and ultrasound images [32], and in pathomorphology [33] and genomics [34]. AI is a promising tool that can be used to trace contacts during the pandemic, to improve pneumonia diagnostics [35], or to monitor COVID-19 patients [36].…”
Section: Introductionmentioning
confidence: 99%
“…The encouragement of semisupervised learning as well as self-supervised learning could prompt the utilization of AI in arrhythmia more widely, as a self-supervised learning method only requires the operator to input a small number of typical data in order for computers to be able to automatically extract unlabeled data without supervision (26,27). Its application eliminates the need for manual recognition and, in the foreseeable future, could probably become mature enough to be utilized in in-hospital monitoring, radiofrequency ablation operations, and portable devices (28). For patients with angina, this monitoring could not only monitor the onset of myocardial infraction (MI), but could also help in predicting it.…”
mentioning
confidence: 99%